PELUANG KERJA ANIMATOR DI INDUSTRI ANIMASI PADA MASA PANDEMI - Rahmawati, Hestin; Mahaniiya, Ni Kadek Nathi Sharma; Artha, I Gede Agus Indram Bayu (Pusat Penerbitan LPPM ISI Bali, 2024)
The COVID-19 pandemic has had a significant impact on various industry sectors, including the animation industry. This research aims to explore the employment opportunities for animators during the pandemic and how adaptation is happening in the industry. Data was obtained through a literature review as well as interviews with several professional animators and industry players. The results show that despite the global economic slowdown, the demand for digital content, including animation, has increased significantly. This is driven by the increasing need for digital-based entertainment and educational content during quarantine. In addition, the animation industry is able to adapt quickly through remote working and online collaboration, which opens up opportunities for animators to remain productive amidst challenging situations. This study concludes that the pandemic accelerates the digital transformation of the animation industry and opens up new opportunities for animators who are able to innovate and adapt to the latest technology.